Analysis of the Turnover Tendency of College Teachers From the Perspective of Psychology - Zhao, Ying; Zhou, Kai (Frontiers in Psychology, 2022)
University teachers are the core of university teaching and scientific research construction and an important link of double first-class construction. The turnover tendency of university teachers is a universal social phenomenon without the characteristics of value judgment. This research study aimed at the problem of college teachers turnover tendency , through to the college teachers turnover tendency and the exploration of psychological mechanism, set up the questionnaire of university teachers, to collect the university teachers to work and the data of turnover tendency , and then build regression model equation to turnover mood psychological tendency to the faculty of quantitative analysis, the final integration of the basic psychological needs theory, the psychological contract theory and the theory of cognitive psychology to explore college teachers psychological mechanism of emotional mood, from the aspects such as teachers' job stress and positive mood to change, On this basis, corresponding countermeasures are put forward to build a support system for the development of college teachers' flow and improve the current situation of the loss of college teachers.